Do foreign institutions improve stock liquity? - WEI, Chi Shen (Institutional Knowledge at Singapore Management University, 2010)
This paper examines whether capital flows by foreign institutions improve liquidity in domestic markets. I find that stocks with increased foreign institutional ownership subsequently experience higher liquidity. However, it is difficult to interpret this evidence as a causal relation because institutions tend to self-select into more liquid stocks. To solve this problem, I exploit the 2003 US dividend tax cut as a natural experiment. The results from a 2SLS (IV) regression confirm that liquidity improved more in dividend-paying stocks located in US tax-treaty countries compared to similar stocks located in non-treaty countries. These patterns are consistent with the notion that institutions improve liquidity through a variety of channels including information competition and greater liquidity trading.